PREVENTION AND ERADICATION OF WHITE-COLLAR CRIMES USING POLICY AND VALUE APPROACHES - Riswan Erfa (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
Based on today’s factual condition, the corruption perceptions index of Indonesia is still very poor Corruption, as part of white-collar crimes, is considered as one of non-conventional crimes which are difficult to overcome using conventional counter-measures. The qualification of the perpetrators who have high socio-economic strata often complicates the law enforcement process, especially in terms of proof. Therefore, it requires a new paradigm that prioritizes policy approach and value approach. And both of the approaches should be done simultaneously. It is also necessary to understand the types of white-collar crimes to support the implementation of policy approach and value approach. In addition, this study also discusses non-penal efforts that can maintain the views of integrity, morality, and professional responsibility of the people who have the potential to engage in white-collar crimes, primarily through the internalization of local wisdom that supports the eradication and prevention of criminal acts of corruption.